Resonance enhancement in laser-produced plasmas : concepts and applications - Ganeev, Rashid A. (John Wiley & Sons, 2018)
A comprehensive guide to a new technology for enabling high-performance spectroscopy and laser sources Resonance Enhancement in Laser-Produced Plasmas offers a guide to the most recent findings in the newly emerged field of resonance-enhanced high-order harmonic generation using the laser pulses propagating through the narrow and extended laser-produced plasma plumes. The author-a noted expert in the field-presents an introduction and the theory that underpin the roles of resonances in harmonic generation. The book also contains a review of the most advanced methods of plasma harmonics generation at the conditions of coincidence of some harmonics, autoionizing states, and some ionic transitions possessing strong oscillator strengths. Comprehensive in scope, this text clearly demonstrates the importance of resonance-enhanced nonlinear optical effects leading to formation of efficient sources of coherent extreme ultraviolet radiation that can be practically applied. This important resource: -Puts the focuses on novel applications of laser-plasma physics, such as the development of ultrashort-wavelength coherent light sources -Details both the theoretical and experimental aspects of higher-order harmonic generation in laser-produced plasmas -Contains information on early studies of resonance enhancement of harmonics in metal-ablated plasmas -Analyzes the drawbacks of different theories of resonant high order harmonic generation -Includes a discussion of the quasi-phase-matching and properties of semiconductor plasmas Written for researchers and students in the fields of physics, materials science, and electrical engineering who are interested in laser physics and optics, Resonance Enhancement in Laser-Produced Plasmas offers an introduction to the topic and covers recent experimental studies of various resonance processes in plasmas leading to enhancement of single harmonic.